Patterns of Tobacco Use and Dual Use in US Young Adults: The Missing Link between Youth Prevention and Adult Cessation. (14th May 2012) - Rath, Jessica M.; Villanti, Andrea C.; Abrams, David B.; Vallone, Donna M.
Abstract : Few studies address the developmental transition from youth tobacco use uptake to regular adulthood use, especially for noncigarette tobacco products. The current study uses online panel data from the Legacy Young Adult Cohort Study to describe the prevalence of cigarette, other tobacco product, and dual use in a nationally representative sample of young adults aged 18–34 (N = 4, 201 ). Of the 23% of young adults who were current tobacco users, 30% reported dual use. Ever use, first product used, and current use were highest for cigarettes, cigars, little cigars, and hookah. Thirty-two percent of ever tobacco users reported tobacco product initiation after the age of 18 and 39% of regular users reported progressing to regular use during young adulthood. This study highlights the need for improved monitoring of polytobacco use across the life course and developing tailored efforts for young adults to prevent progression and further reduce overall population prevalence.